Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-53655-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disorder prenatal diagnosis and pregnancy termination practices among high consanguinity population, Saudi Arabia

Abstract: The prevalence of consanguineous marriage and genetic disorders are high in Saudi Arabia. There were records on the practices of Saudis toward prenatal diagnosis (PND) and termination of pregnancy (TOP), however the sample sizes are small. This study has targeted the Saudi Arabian community and family history of genetic disorders to determine the practices toward PND and TOP. The cross-sectional survey was conducted among Saudis (n = 2761) to determine their practices toward reproductive-decision making. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In the UK, a mid-pregnancy or anomaly scan is usually carried at the 20th week of pregnancy, which leads to a late diagnosis of some fetal malformations, such as anencephaly, omphalocele, and limb anomalies that can be detected earlier at 10-14 weeks of pregnancy [42][43][44]. Better diagnostics procedures (such as Magnetic Resonance Imaging (MRI), genetic testing, Molecular testing of the chorionic villus sample (CVS) or amniocytes, fetal blood sample, a direct biopsy of fetal tissue, and Non-invasive prenatal diagnosis (NIPD)) help in the early detection of congenital anomalies during the perinatal period (earlier than 20 weeks of pregnancy and during the first trimester) [45,46], which facilitate early informed decision-making, including the option of early pregnancy termination and thus, decrease the probability of having newborns with congenital anomalies and its associated complications and hospitalisation. Termination of pregnancy practices differ from country to another based on their own regulations.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, a mid-pregnancy or anomaly scan is usually carried at the 20th week of pregnancy, which leads to a late diagnosis of some fetal malformations, such as anencephaly, omphalocele, and limb anomalies that can be detected earlier at 10-14 weeks of pregnancy [42][43][44]. Better diagnostics procedures (such as Magnetic Resonance Imaging (MRI), genetic testing, Molecular testing of the chorionic villus sample (CVS) or amniocytes, fetal blood sample, a direct biopsy of fetal tissue, and Non-invasive prenatal diagnosis (NIPD)) help in the early detection of congenital anomalies during the perinatal period (earlier than 20 weeks of pregnancy and during the first trimester) [45,46], which facilitate early informed decision-making, including the option of early pregnancy termination and thus, decrease the probability of having newborns with congenital anomalies and its associated complications and hospitalisation. Termination of pregnancy practices differ from country to another based on their own regulations.…”
Section: Discussionmentioning
confidence: 99%
“…3 Specific information on the prevalence of SCD in Saudi Arabia is inconsistent; however, data derived from the Saudi Premarital Screening Program database, which includes 488,315 individuals, indicated that 4.2% of the screened population has the sickle cell trait and 0.26% of these individuals have sickle cell disease. 4 The high prevalence of SCD in Saudi Arabia is because of substantial consanguinity among first cousins (>50% of total marriages) [5][6][7] and general knowledge of genetics in Arab countries lacks understanding the fundamental characteristics of genetic diseases. 6 Sickle cell disease is a hereditary anaemia that results from the presence of a mutated form of haemoglobin, haemoglobin S, which causes red blood cells to become rigid, sticky and misshapen.…”
mentioning
confidence: 99%
“…4 The high prevalence of SCD in Saudi Arabia is because of substantial consanguinity among first cousins (>50% of total marriages) [5][6][7] and general knowledge of genetics in Arab countries lacks understanding the fundamental characteristics of genetic diseases. 6 Sickle cell disease is a hereditary anaemia that results from the presence of a mutated form of haemoglobin, haemoglobin S, which causes red blood cells to become rigid, sticky and misshapen. 1 HbS arises from a mutation substituting thymine for adenine in the sixth codon of the beta-chain gene.…”
mentioning
confidence: 99%
“…The molecular mechanism behind the death of the fetus in relation to the homozygous NM_017419.3:c.680G>T at exon 4 (ASIC5 Saudi ) in the ASIC5 gene should be studied in detail. Early prenatal diagnosis of pathogenic variation like ASIC5 Saudi can provide a choice for the parent to decide pregnancy termination within the allowed time among high-consanguinity population (60). and encouragement.…”
Section: Discussionmentioning
confidence: 99%